Analysis of Thermo-Hydro-Mechanical Coupling of Coal and Gas with Absorption/Desorption Thermal Effect. (23rd December 2020) - Hao, Jianfeng; Liang, Bing; Sun, Weiji
Abstract : Coal adsorption/desorption gas can cause temperature changes. Moreover, the pressure difference between the high gas pressure area and the low gas pressure area in the coal may affect the coal adsorption/desorption gas thermal effect. To study the effect of adsorption/desorption thermal effect on the evolution law of coal and gas outburst precursor information under different pressure differences, the adsorption/desorption thermal effect experiments were carried out. And the thermo-hydro-mechanical coupling model was established, which reflects the interaction between coal and gas. Under the action of ground stress, pore pressure, adsorption expansion stress, and thermal expansion stress, the model includes the dynamic evolution of coal porosity and permeability, gas adsorption-desorption-diffusion-seepage, and energy accumulation and dissipation. Using the coupling model, the mechanism of adsorption/desorption thermal effect on the evolution of outburst precursor information and the mutual coupling relation between coal and gas is analyzed. The experimental results show that the relation between pressure difference and coal sample temperature variation is linear, and the pressure difference has a quadratic parabolic relation with the temperature accumulation of coal sample. As the pressure difference increases, the temperature variation of the coal sample gradually increases, but the temperature accumulation gradually decreases. Numerical simulation results show that as the pressure difference increases, the changes in coal temperature and gas pressure gradually decrease, and the thermal expansion strain caused by the adsorption/desorption thermal effect decreases, and the permeability increases. Comparing the calculation results with or without the adsorption/desorption thermal effect, the volumetric strain, temperature, and permeability of the coal have significant changes when the adsorption/desorption thermal effect is considered, and the gas drainage volume increases as the pressure difference increases. The effect of thermal expansion strain caused by adsorption/desorption thermal effect on gas seepage is greater than the effect of temperature change on gas seepage.